Epidemiology of Mansonella perstans in the middle belt of Ghana. Issue 1 (December 2017) - Debrah, Linda; Nausch, Norman; Opoku, Vera; Owusu, Wellington; Mubarik, Yusif; Berko, Daniel; Wanji, Samuel; Layland, Laura; Hoerauf, Achim; Jacobsen, Marc; Debrah, Alexander; Phillips, Richard
Abstract Background Mansonellosis was first reported in Ghana by Awadzi in the 1990s. Co-infections ofMansonella perstans have also been reported in a small cohort of patients with Buruli ulcer and their contacts. However, no study has assessed the exact prevalence of the disease in a larger study population. This study therefore aimed to find out the prevalence ofM. perstans infection in some districts in Ghana and to determine the diversity ofCulicoides that could be potential vectors for transmission. Methods From each participant screened in the Asante Akim North (Ashanti Region), Sene West and Atebubu Amantin (Brong Ahafo Region) districts, a total of 70 μl of finger prick blood was collected for assessment ofM. perstans microfilariae. Centre for Disease Control (CDC) light traps as well as the Human Landing Catch (HLC) method were used to assess the species diversity ofCulicoides present in the study communities. Results From 2, 247 participants, an overall prevalence of 32% was recorded although up to 75% prevalence was demonstrated in some of the communities.Culicoides inornatipennis was the only species ofCulicoides caught with the HLC method. By contrast, C. imicola (47%), C. neavei (25%) andC. schultzei (15%) were caught by the CDC light trap method. A wide diversity of otherCulicoides spp. was also identified but correlation was only found between the prevalence ofC. inornatipennis andM. perstans during the dry season. Conclusions Here we demonstrate for the first time thatM. perstans is highly prevalent in three districts in Ghana. We found a wide spectrum ofCulicoides spp.Culicoides inornatipennis was the most anthropophilic and is therefore likely to be the species responsible for transmission of infection but formal proof has yet to be obtained. Trial registration NCT02281643 . Registered October 26, 2014. 'Retrospectively registered'. Trial Registry: ClinicalTrials.gov.